2008
DOI: 10.1002/cne.21682
|View full text |Cite
|
Sign up to set email alerts
|

Local circuitry in the anterior caudal lobe of the mormyrid cerebellum: A study of intracellular recording and labeling

Abstract: The caudal lobe of the mormyrid cerebellum includes the anterior portion, which is associated with the lateral line and eighth nerve senses, and the posterior portion, which is associated with the electrosense. This study examines the physiology and morphology of cells in the anterior portion in slice preparations. Two subtypes of Purkinje cells, efferent cells and stellate cells, are described. Multipolar Purkinje cells are located in the central region of the lobe, with large, multipolar, spiny dendrites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Our previous work also showed that in an fPC, the regions occupied by PFs and the single CF are clearly separated spatially (Han et al 2006), and that this is also the case for mPCs (Zhang et al 2008), Such a separation of inputs facilitates their selective activation, and we have shown this to be true for both PC subtypes (Fig. 2, A 2 and B 2 ).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Our previous work also showed that in an fPC, the regions occupied by PFs and the single CF are clearly separated spatially (Han et al 2006), and that this is also the case for mPCs (Zhang et al 2008), Such a separation of inputs facilitates their selective activation, and we have shown this to be true for both PC subtypes (Fig. 2, A 2 and B 2 ).…”
Section: Resultssupporting
confidence: 79%
“…The large multipolar cells have been classified as PCs on the basis of their morphology and connectivity (Bell and Szabo 1986;Campbell et al 2007). As shown in our previous work, PF and CF synapses onto mPCs are spatially segregated (Zhang et al 2008), with CF terminals apposed to the soma and proximal dendritic regions, and PFs making synaptic contacts largely in the distal dendrites. By careful positioning and repositioning of the stimulation electrodes, PFs and an mPC's single CF can be selectively activated, as shown in Fig.…”
Section: Associative Long-term Potentiation At Parallel Fiber Synapses Onto Mpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological and physiological studies have suggested that the cerebellar inputs and outputs in teleost fish are similar to those in mammals [21,22]. Furthermore, intrinsic cerebellar circuitry in teleost fish shares basic features with that in mammals [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of the cerebellum in emotional learning in teleost fish is poorly understood, whereas the cerebellum obviously shares major intrinsic circuitry, as well as afferent and efferent connections with other brain parts, with those in the mammalian cerebellum [19-22]. …”
Section: Introductionmentioning
confidence: 99%